Competitiveness Improvement in BUMDes Through Marketing Digitalization - Ghofar, Abdul; Handaru, Wuri Cahya; Riza, Muhammad Faisal; Umam, Khoirul; Kusumadewi, Areta Widya; Larasati, Wahyu Kartika; Nafi’a, Insania; Aqila, Hafizh; Maharani, Cevira Dewi; Pratama, Fadhil Irvan; Jawo, Muhammed (The International Journal of Accounting and Business Society, 2023)
Purpose — The objectives of this research are (1) to create digital marketing strategies using SWOT analysis, (2) to create information channels as digital marketing media using websites, and (3) to strengthen the image and governance of BUMDes Mitra Sejati of Kucur village, which has managed several business units and was affected by the COVID-19 pandemic. Design/methodology/approach — This research uses the qualitative method with the case study and interview approach, so the results are analytical and descriptive in nature. The population of this research is Village-Owned Enterprises throughout Indonesia, and the sample is BUMDes Mitra Sejati, a village-owned enterprise located in Kucur village of Dau sub-district in Malang regency. The village government manages this organization. Findings—BUMDes Mitra Sejati's growth is hampered by ineffective governance, the unavailability of suitable marketing and promotion media for the village's products and tourist destinations, and poor product branding and innovation. Practical implications — This research helps the enterprise optimize digital marketing, which other BUMDes in Indonesia. can also utilize Originality/value — This article presents a case of digital marketing applied by BUMDes in Indonesia so that it can provide an example of the sub-optimal use of digital marketing that reduces BUMDes revenue. Paper type — Case study